DETERMINATION OF BASIC THEORETICAL DEFINITIONS OF RESTAURANT BUSINESS IN THE SYSTEM OF PUBLIC ADMINISTRATION - Balandina, Iryna (Theory and Practice of Public Administration, 2020)
The article is devoted to topical issues of development of the restaurant management system. Given the increasing role of the service sector in the structure of the country’s economy, it is important to create conditions through the implementation of public sector governance mechanisms for the development of private sector activity. The restaurant industry is one of the most attractive investment areas and provides the development of related industries. In addition, the restaurant industry has a high social impact through the implementation of the functions of providing healthy and complete nutrition to various segments of the population, including children, people of working age, people undergoing treatment or rehabilitation, etc. Therefore, despite the high commercialization of the industry, because of the high social role it plays in the country’s economy, it is important to ensure state support and create opportunities for its development. Due to its specificity, the restaurant industry contributes to improving the working capacity of the population and can therefore contribute to economic development. The article analyzes the theoretical approaches to defining the concept of restaurant industry, both at the legislative level and through the analysis of modern scientific periodicals, taking into account the trends and trends of the restaurant industry. The accumulation of regulatory legal frameworks for the regulation of the restaurant system has made it possible to determine the basis of regulatory support for the restaurant system in Ukraine. However, the analysis of the legislative system on the theoretical substantiation of the basic concepts of the restaurant industry showed that these definitions do not fully reflect the systematic nature of the industry and reflect its specificity, which needs further analysis and development. By defining the specifics of management in the restaurant industry, the problematic aspects of providing the theoretical and methodological basis for its development were outlined. As a result of the analysis, ways of taking into account the specific characteristics of the restaurant system in the structure of state management of economic processes were proposed in order to ensure state support for the development of the restaurant industry, taking into account its investment attractiveness and social role.